2015
DOI: 10.1080/08111146.2014.990626
|View full text |Cite
|
Sign up to set email alerts
|

Health, Transport and Urban Planning: Quantifying the Links between Urban Assessment Models and Human Health

Abstract: We developed two simple, effective and consistent methods for predicting human health outcomes from physical activity in a typical urban development at a precinct scale. Considering the two primary transport outputs from an urban assessment model (vehicle kilometres travelled and mode share), we developed two methods using approaches based on the literature linking human health outcomes and transport. The two methods were applied to a case study and generated very similar results, demonstrating how a human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…This figure was roughly translated to a health care cost savings of $44 million (Australian dollars) over the next 50 years, to go along with a benefit of $402 million to the economy as a result of improved economy. Also working in the Perth metropolitan area, Matan et al (2015) demonstrated another back-of-the envelope method for estimating the monetary value of transit-related health benefits. Based on previous studies, they assumed that each additional public transit user walked an additional 15 minutes each day, and the health benefits of this additional activity were valued at $3.24 (Australian dollars) per hour.…”
Section: Health Care Costs With a Focus On Physical Activity And Tmentioning
confidence: 99%
“…This figure was roughly translated to a health care cost savings of $44 million (Australian dollars) over the next 50 years, to go along with a benefit of $402 million to the economy as a result of improved economy. Also working in the Perth metropolitan area, Matan et al (2015) demonstrated another back-of-the envelope method for estimating the monetary value of transit-related health benefits. Based on previous studies, they assumed that each additional public transit user walked an additional 15 minutes each day, and the health benefits of this additional activity were valued at $3.24 (Australian dollars) per hour.…”
Section: Health Care Costs With a Focus On Physical Activity And Tmentioning
confidence: 99%
“…Seeking remedies, many North American researchers have looked to Europe for potential strategies, finding examples of successful practices in the walkability and cycleinclusive strategies applied in specific cities, such as Freiburg and Copenhagen. Many key authors emphasise the need for integral, ecological approaches that place a high priority on social participation in decision-making and implementation, to optimise the potential success of these very challenging transitions (Banister, 2008;Buehler & Pucher, 2011;Evans & Karvonen, 2011;Gehl & Gemzo, 1996Kenworthy, 2006;Newman & Jennings, 2008;Newman, Beattie, Trubka, & Selvey, 2015;Sagaris, Tiznado-Aitken, & Steiniger, 2017;Smith, 2011). To date, many of these efforts have been applied in the Complete Street agenda (Hui, Saxe, Roorda, Hess, & Miller, 2018;McCann, 2013;Smart Growth America & National Complete Streets Coalition, 2015), which aims to create streets that are safer, more vibrant and inclusive (in terms of the variety of both transport modes and users).…”
Section: Introductionmentioning
confidence: 99%
“…This study did not consider studies where it was not possible for a reader to calculate the embodied GHG emissions separately from operational emissions (Åkerman 2011, Pan et al 2013, Tarnoczi 2013, Warren and Ieromonachou 2013, Timmermann and Dibdiakova 2014, Matan et al 2015, Steffen et al 2015, Krezo et al 2016, Dalkic et al 2017 or studies which did not consider non-operational emissions ( The final body of literature consisted of 22 publications, including 57 unique infrastructure cases, which were used to develop a database reporting the key elements of published embodied GHG assessment in rail infrastructure. Since the data were collected by the authors of the respective publications, they are considered as secondary data (Irwin 2013).…”
Section: Selection Of Reviewed Papersmentioning
confidence: 99%